2020
DOI: 10.1007/s00710-020-00709-9
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared spectroscopy of alkali feldspar samples for space application

Abstract: Feldspars are major components of terrestrial planetary surfaces. For future space application and the setup of a comprehensive reference database, Na- and K-rich alkali feldspars, NaAlSi3O8 – KAlSi3O8, have been investigated by infrared reflectance spectroscopy. We related the feldspar spectra to the chemical composition and state of Al,Si order/disorder. The infrared measurements were analyzed with respect to band shifts and peak shapes using the autocorrelation function. Natural samples served as starting m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Due to their intrinsic spectral complexity, detailed studies of the complete crystallographic and compositional range are necessary. Our investigations of the Na-and K-rich alkali feldspars showed that the autocorrelation method allows differentiating between the compositional and the order/disorder influences seen in the powder reflectance spectra in the wavelength range between 7 µm to 14 µm (Reitze et al 2020). In particular, decreasing the degree of order led to broader RBs and a feature shift.…”
Section: Synthetic Glassesmentioning
confidence: 85%
See 2 more Smart Citations
“…Due to their intrinsic spectral complexity, detailed studies of the complete crystallographic and compositional range are necessary. Our investigations of the Na-and K-rich alkali feldspars showed that the autocorrelation method allows differentiating between the compositional and the order/disorder influences seen in the powder reflectance spectra in the wavelength range between 7 µm to 14 µm (Reitze et al 2020). In particular, decreasing the degree of order led to broader RBs and a feature shift.…”
Section: Synthetic Glassesmentioning
confidence: 85%
“…Another crucial Mercury surface analog are feldspars (Helbert et al 2007;Sprague et al 2009;Reitze et al 2020). Due to their intrinsic spectral complexity, detailed studies of the complete crystallographic and compositional range are necessary.…”
Section: Synthetic Glassesmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations of the plagioclases from the Lappajrvi crater, Finland, revealed an almost highest possible degree of disorder, showing a complex interaction of shock and the impact melt (Bischoff & Stffler, 1984). Simulated micrometeorite bombardment with laser irradiation of powder pressed pellets leads to a decrease of spectral contrast of the Reststrahlen bands (RBs) of plagioclase feldspar samples and a formation of smaller grain sizes due to a gardening process, which disturbs the flat surface of the pellets (Moroz et al, 2014;Weber et al, 2020).…”
Section: Accepted Articlementioning
confidence: 99%
“…The autocorrelation technique is sensitive to the width of the analyzed peaks in the spectra. Reitze et al (2020) and Reitze et al (2021) used the autocorrelation method to analyze mid-IR reflectance spectra and were able to determine the degree of Al,Si order of alkali feldspars as well as plagioclase feldspars with the technique. The method uses the wavelength of the CF and the width of the spectral autocorrelation function between 7.27 µm and 12.11 µm (Reitze et al, 2021).…”
Section: Infraredmentioning
confidence: 99%